2017
DOI: 10.1177/2041669517715474
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Ratings of Beauty and Aesthetics: Correlations With Statistical Image Properties in Western Oil Paintings

Abstract: For centuries, oil paintings have been a major segment of the visual arts. The JenAesthetics data set consists of a large number of high-quality images of oil paintings of Western provenance from different art periods. With this database, we studied the relationship between objective image measures and subjective evaluations of the images, especially evaluations on aesthetics (defined as artistic value) and beauty (defined as individual liking). The objective measures represented low-level statistical image pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 46 publications
1
56
0
Order By: Relevance
“…On the other hand, Forsythe et al [9] found a stronger relationship between a combination of their image complexity statistics (GIF image size and fractal dimension) and beauty ratings (42% shared variance). However, a recent paper [10] found no more than 5.6% shared variance between their artwork statistics and ratings. When analyses were performed separately for artworks containing different subjects, shared variance increased, and was highest for flowers/vegetation (13%) and for buildings (25.3%).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, Forsythe et al [9] found a stronger relationship between a combination of their image complexity statistics (GIF image size and fractal dimension) and beauty ratings (42% shared variance). However, a recent paper [10] found no more than 5.6% shared variance between their artwork statistics and ratings. When analyses were performed separately for artworks containing different subjects, shared variance increased, and was highest for flowers/vegetation (13%) and for buildings (25.3%).…”
Section: Introductionmentioning
confidence: 94%
“…When analyses were performed separately for artworks containing different subjects, shared variance increased, and was highest for flowers/vegetation (13%) and for buildings (25.3%). Other recent research has focused on identifying clusters of participants who share common statistical preferences [10][11][12] The variable success of attempts to identify simple statistical measures of universal beauty is not surprising given that artworks vary along multiple visual dimensions and in terms of their semantic content: as well as containing luminance and colour variation at a range of spatial scales, artworks also often contain meaningful subject matter, such as a landscape, a human face or other biological forms. Given this complexity, beauty ratings may depend on a combination different image statistics rather than a single statistic, and the relevant combination of statistics may vary across subject matter.…”
Section: Introductionmentioning
confidence: 99%
“…They allow the creation of models that can analyze any picture and predict their aesthetic value, without the need for any annotated data about its contents; and without making use of hand-crafted features. Some examples of the use of CNNs for image aesthetics prediction and related topics can be found in [2,20,33,6,11,4,9,35,10,17]. Some of those papers make use of information about the contents of the pictures to improve the predictions of the models.…”
Section: Related Work 21 Computational Aesthetic Assessment In Photomentioning
confidence: 99%
“…The features in which the piece of art can be described with will, therefore, explain only a small part of the preferences of human perceivers over aesthetics in art. Nevertheless, it has been suggested that there is some shared perception of beauty and aesthetics in art [11], which suggests that there are features that computational models can learn which account for this shared perception of beauty.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of the quality of goods is based on human feelings in many areas, such as works of art [1,2], consumer electronics [3,4], cars [5,6], and other products [7,8]. Subjective evaluations are as important as objective metrics for engineering products because consumers evaluate the value of products based on their feelings.…”
Section: Introductionmentioning
confidence: 99%